Gibraltar - Remiro Brotóns, Antonio (Cuadernos de Gibraltar – Gibraltar Reports, 2018)
I. HISTORICAL BACKGROUND – II. GIBRALTARAND DECOLONIZATION: THE UNITED NATIONS RESOLUTIONS – III. HISPANO-BRITISHNEGOTIATIONS IN 1966: RUPTURE AND CONFRONTATION – IV. DEMOCRATIC SPAIN: FROM THE 1980 LISBON TO THE 1984 BRUSSELS AGREEMENT – V. FROM THE MATUTES PROPOSAL (1997) TO THE UNSUCESSFULL NEGOTIATIONS OF 2001-2002 – VI. A NEW CONSTITUTION FORGIBRALTARAND ATRIPARTITE FORUM FOR NEGOTIATION – VII. LEGAL CONCLUSIONS – VIII. LOOKING TOWARD THE FUTURE – IX. BIBLIOGRAPHY.